Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Pada Unit Pelayanan Teknis Puskesmas Naioni Kota Kupang - Vera Herlina Mustari (Jurnal Manajemen, 2022)
This study aims to determine (1) the significant effect of direct evidence, reliability, responsiveness, assurance, and empathy both partially and simultaneously on patient satisfaction at UPT Puskesmas Naioni Kupang City; (2) the dimension with the most dominant influence on patient satisfaction. The research sample was 99 patients. Samples were determined using the Slofin formula. Data were collected with the main instrument, namely a questionnaire. The data analysis technique used Multiple Linear Regression. The results showed that (1) direct evidence, reliability, responsiveness, assurance, and empathy had a significant effect either partially or simultaneously on patient satisfaction at UPT Puskesmas Naioni Kupang City; (2) Responsiveness has the most dominant influence on patient satisfaction